2016
DOI: 10.5194/acp-2016-768
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Terpenoid, acetone and aldehyde emissions from Norway spruce

Abstract: <p><strong>Abstract.</strong> We present spring and summer volatile organic compound (VOC) emission rate measurements from Norway spruce (<i>Picea abies</i> L. Karst) growing in a boreal forest in southern Finland. The measurements were conducted using in situ gas-chromatograph with 1 to 2-hour time resolution. The measurements cover altogether 14 weeks in years 2011, 2014 and 2015. Monoterpene (MT) and sesquiterpene (SQT) emission rates wer… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Moreover, individual pine and spruce trees produce and emit conspicuous, tree-specific monoterpene blends (Schönwitz et al 1990a;Bäck et al, 2012;Hakola et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, individual pine and spruce trees produce and emit conspicuous, tree-specific monoterpene blends (Schönwitz et al 1990a;Bäck et al, 2012;Hakola et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Bäck et al (2012) showed that Scots pine trees of the same age, growing in the same environment, emit very different monoterpene selections. This has also been found to be true in the emissions of Norway spruce (Hakola et al, 2017). When considering the atmospheric impact of biogenic emissions, it is essential to know the speciesspecific composition of the emission, because for example atmospheric reactivity and aerosol formation potential of different compounds varies a lot (e.g.…”
Section: Introductionmentioning
confidence: 93%
“…The data include earlier measurements from 2011, 2014 and 2015 that has been published in Hakola et al (2017) and new measurements from 2019 and 2021. In 2021, the measurements covered two different trees.…”
Section: Experimental 11 Measurement Sites and Earlier Emission Measu...mentioning
confidence: 99%
See 2 more Smart Citations